Electromagnetic Wave Absorption Performance of Ni0.7Zn0.3Fe2O4/Zeolite/ CNT-Epoxy Polymer Matrix at Different Thickness - Fadzidah Mohd Idris; Muhammad Aqil Haziq Mohd Zamri; Ahmad Haziq Mohamed Sabri; Faisal Abdul Rahman; Ts. Dr. Hatika Kaco; Mohd Shamsul Ezzad Shafie (Semarak Ilmu Publishing, 2025)
Indexed